The Use of Levosimendan in the Treatment of Neurogenic Stress Cardiomyopathy in a Patient with Nontraumatic Subarachnoid Hemorrhage (Case Report) - A. A. Polupan; T. F. Tabasarankiy; A. S. Kheireddin; I. A. Savin; O. M. Zelenkova; Ya. V. Savchenk; T. M. Birg; A. A. Pashin; A. A. Sychev; A. I. Baranich; O. B. Belousova (Общая реаниматология, 2021)
We present a case of cardiogenic shock due to neurogenic stress cardiomyopathy (NSC) in a patient with nontraumatic subarachnoid hemorrhage caused by a ruptured aneurysm of the right pericallosal artery. Due to the catecholamine-resistant shock, levosimendan was administered under advanced hemodynamic control, including transpulmonary thermodilution and echocardiography. This resulted in an improved cardiac contractility and reduced demand for catecholamines. Full stabilization of hemodynamic parameters was achieved by day 5. In the discussion section we reviewed available published case reports of using levosimendan in stress cardiomyopathy treatment.